Global, regional, and national anemia burden among women of reproductive age (15–49 years) from 1990 to 2021: an analysis of the Global Burden of Disease Study 2021 - Zheng, Wenshuai; Peng, Bo; Wu, Yamei; Gauan, Lixun; Wang, Shenyu; Ning, Hongmei (Frontiers in Nutrition, 2025)
BackgroundAnemia remains a significant global health challenge, disproportionately affecting women of reproductive age (WRA, 15 to 49 years) due to physiological and socioeconomic factors. However, there is a lack of high-quality data on anemia burden and causes analysis in this population. The aim of this study is to provide a comprehensive global assessment of anemia burden and its underlying causes among WRA.MethodsUsing data from the Global Burden of Disease Study (GBD) 2021, we evaluated the prevalence, years lived with disability (YLDs), and underlying causes of anemia among WRA at global, regional, and national levels. We also evaluated the association between anemia burden and the socio-demographic index (SDI), quantified temporal trends of anemia burden from 1990 to 2021, and projected future burden to 2030.ResultsGlobally in 2021, there were 657.09 million (95% uncertainty interval [UI]: 643.59 to 671.22) anemia cases and 18.07 million (95% UI: 12.00 to 26.17) YLDs among WRA. The global age-standardized prevalence rates (ASPR) and YLDs rates per 100,000 were 33,716.77 (95% UI: 33,023.84 to 34,441.71) and 927.03 (95% UI: 615.40 to 1,342.99) in 2021, and they decreased by 0.181% and 0.539% annually from 1990 to 2021, respectively. However, the decline in ASPR stagnated after 2009, with a slight increase observed through 2021, primarily driven by rising mild anemia. An inverse relationship existed between SDI and anemia burden across regions and nations. The most common causes of anemia were dietary iron deficiency, hemoglobinopathies and hemolytic anemias, and other neglected tropical diseases, with HIV/AIDS and malaria being most prominent in specific regions. Projections indicate anemia cases and YLD counts will rise consistently from 2022 to 2030, while ASPR and age-standardized YLD rates will decline.ConclusionAnemia among WRA is a major public health burden worldwide with persistent regional and socioeconomic disparities. Mitigating this burden requires continued efforts addressing underlying causes, reducing socioeconomic inequities, and improving access to healthcare and nutritional interventions.